(untitled) (Health Renaissance, 2015)
Introduction: Epilepsy is a common health problem which engenders a variety of medical, social, psychological and economic burdens. Stereotyped assumptions about people with conditions such as epilepsy are inherent in many cultures and Nepal is not exception .Better information about epilepsy among the people can remove the stigma associated with it. Objective: The aim of the present study was to assess the knowledge, attitude and stigma regarding epilepsy among patients with epilepsy. Methods: It is a hospital based, cross-sectional descriptive study of 47 patients visiting BPKIHS psychiatry OPD. A semi structured Proforma, knowledge attitude questionnaire and the Stigma Scale developed by M. King et.al. Was administered to collect the data. Results: Majority (66.0%) of subjects were male. Generalized seizure (76.6%) was most common presentation. Majority of subjects believed that their disease should be kept secret. Almost 81% subjects thought they could work with persons suffering from epilepsy whereas 23.4% subjects objected even to travel together with them. About 32% subjects felt bad about having epilepsy, 40.4% agreed that they were angry the way people react to their illness, and 76.6% thought that they would have had better chances in life if they did not have epilepsy. Conclusion: Knowledge about epilepsy is still patchy among patients. Despite this, attitude towards epilepsy is generally positive. Still there is significant stigma attached to this illness. These findings call for comprehensive educational program aimed at improving the knowledge and reducing the stigma in the population at large. DOI: http://dx.doi.org/10.3126/hren.v12i1.11979 Health Renaissance 2014;12(1):11-17